The activities of the experimental demonstration school-commune in Samarkand - Asatullayev Mirzhalohon Isakhonovich (Genius Journals, 2022)
This article provides information on the activities of an experimental community school in Samarkand.
Keywords: School-commune; education; boarding school; club activities